Metformin Alleviates Neuroinflammation Following Intracerebral Hemorrhage in Mice by Regulating Microglia/Macrophage Phenotype in a Gut Microbiota-Dependent Manner - Yu, Xiaobo; Fu, Xiongjie; Wu, Xinyan; Tang, Wenwen; Xu, Lei; Hu, Libin; Xu, Chaoran; Zhou, Hang; Zhou, Guoyang; Li, Jianru; Cao, Shenglong; Liu, Jiang; et al. (Frontiers in Cellular Neuroscience, 2022)
The gut microbiota plays a key role in regulating intracerebral hemorrhage (ICH)-induced neuroinflammation. The anti-neuroinflammatory effects of metformin (Met) have been reported in many central nervous system (CNS) diseases. However, whether Met regulates neuroinflammation through the gut microbiota in ICH-induced brain injury remains unknown. We found that Met treatment substantially alleviated neurological dysfunction and reduced neuroinflammation by inhibiting pro-inflammatory polarization of microglia/macrophages in mice with ICH. Moreover, Met treatment altered the microbiota composition and improved intestinal barrier function. The expression of lipopolysaccharide-binding protein (LBP), a biomarker of intestinal barrier damage, was also significantly reduced by Met treatment. Neuroinflammation was also potently ameliorated after the transplantation of fecal microbiota from Met-treated ICH mice. The neuroprotective effects of fecal microbiota transplantation (FMT) were similar to those of oral Met treatment. However, suppression of the gut microbiota negated the neuroprotective effects of Met in ICH mice. Therefore, Met is a promising therapeutic agent for neuroinflammation owing to ICH-induced imbalance of the gut microbiota.